Efektivitas Peraturan Pemerintah Nomor 22 Tahun 2022 dalam PerlindunganHukum dan Pemenuhan Hak Awak Kapal Perikanan Migran - Sabrina Sugiatna; Dede Agus; Nuryati Solapari (Journal of Law Perspectives Review, 2025)
Indonesia is a country with abundant marine resources due to the large number of islands in Indonesia,including large and small islands, with approximately 17,508 islands. The high number of islands inIndonesia makes this one of the livelihoods of the Indonesian people, especially those living on thecoastline, namely as fisheries crew members or fishermen. This study aims to analyze the effectiveness ofGovernment Regulation Number 22 of 2022 in providing legal protection and ensuring the fulfillment ofrights for migrant fisheries crew members. The research employs an empirical juridical approach, utilizingliterature review and field studies through direct interviews. The findings reveal that despite the existenceof this regulation, the implementation of legal protection for migrant fisheries crew members remainschallenging. Key issues include weak policy enforcement, limited supervision, lack of legal awarenessamong crew members, and bureaucratic obstacles that hinder access to legal assistance. Additionally,cases of exploitation and labor contract misinterpretation persist, particularly in the high-risk fisheriesindustry. The regulation establishes a clearer legal framework by defining the responsibilities ofplacement companies and the government in ensuring social protection, fair wages, work safety,insurance, and legal aid for crew members. However, gaps in enforcement necessitate collaborative effortsamong government agencies, fisheries companies, and non-governmental organizations. Strengtheningsupervision, legal enforcement, and empowering crew members through legal education and training arecrucial to improving protection. Continuous policy improvements and inter-agency coordination areexpected to enhance the effectiveness of legal protection for migrant fisheries crew members in Indonesia.